Fracture mechanics methods for evaluating the adhesion of cold spray deposits. (January 2019) - White, B.C.; Story, William A.; Brewer, L.N.; Jordon, J.B.
Highlights: The interfacial fracture toughness of AA7075 cold spray deposits was quantified. The mode I fracture toughness was found to correlate with surface roughness. Residual stresses accounted for 35% of the mixed mode I/II interface toughness. Fracture based tests help us understand how flaws affect the adhesion of cold spray. Abstract: The adhesion strength of cold sprayed (CS) AA7075 deposits made with varying surface preparations was measured using two fracture toughness methods, and compared to the more common ASTMC633 adhesion test. The ASTMC633 test was found to be limited by the cohesive strength of the deposit, or most commonly the bond strength of the epoxy used (∼75 MPa). Using a unique interfacial compact tension (CT) specimen, KI, eff values were found to range between 1.25 and 1.90 MPa √m with a linear relationship between the substrate roughness and the interface toughness. A mixed mode I/II four-point bend test found significantly higher interface toughness values of around 4.87 MPa √m, and no clear dependence on surface roughness. Residual stresses were found to cause problems with cracking in the interface CT specimens, and more generally to change the measured adhesion values for all test methods. The deformation of the four-point bend specimens caused by residual stresses allowed for a direct measurement of the effects of residual stresses on the interfacial toughness, which was found to be 35% of the measured value.